Neoliberalism and women in India : governmentality perspectives - Kalpagam, U. (Rawat, 2021)
"This study examines neoliberal strategies of governmentality in India. The author analyzes the effects of globalization and how women's subjectivities are shaped in a variety of sociopolitical contexts"--